PENGEMBANGAN DESAIN STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS EMPATI SOSIAL PADA KULTUR JAWA–MADURA DI SDN MAYANGAN 2 KOTA PROBOLINGGO - Moch. Salman Alfarizi; Musa Asy'arie; Sekar Ayu Aryani; Muthoifin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
The diversity of Javanese and Madurese cultures at SDN Mayangan 2 Probolinggo City shapes the dynamics of students' social interaction which has the potential to cause gaps in social relations and bullying behavior towards minority groups, while research that develops a learning design of Islamic Religious Education based on local culture to build social harmony in the multicultural community of elementary schools is still very limited. This study aims to describe the construction of Javanese-Madura culture, analyze the construction of democratic and multicultural values in the learning of Islamic Religious Education, and develop the design of a learning strategy for Islamic Religious Education based on democracy and multiculturalism rooted in Javanese-Madura culture at SDN Mayangan 2 Probolinggo City. This study uses a qualitative approach with an ethnographic method involving 15 informants consisting of school principals, Islamic Religious Education teachers, classroom teachers, students, and parents, with data collection techniques in the form of participatory observation, in-depth interviews, and documentation studies analyzed using the Spradley ethnographic model. The results of the study show that Javanese-Madura culture forms a pattern of social interaction characterized by the dominance of the majority group, the tendency of cultural grouping, and the practice of bullying against minority groups, while the research output is in the form of a design of a learning strategy for Islamic Religious Education based on democracy and multicultural that integrates cultural exploration, democratic dialogue, multicultural collaboration, and reflection on Islamic values to strengthen tolerance and empathy social harmony and social harmony of students